The Impact Of The Cosmic Verses Of The Word (To Find) And Its Derivatives In Understanding The Quranic Context (Journal of the College of Basic Education, 2024)
In this research, we shed light on the impact of the cosmic verses of the word (find) and its derivatives in understanding the Qur’anic context by extrapolating the cosmic verses, and identifying the role of the Qur’anic context in revealing the connotations, words, and meanings of the word (find) and explaining its derivatives that were mentioned by linguists and commentators, with an indication of many patterns Of the structures and meanings in which I mentioned, and perhaps I succeeded in collecting the fragments of what the researchers overlooked and what its lines were scattered in the stomachs of the books.